1999
DOI: 10.1128/iai.67.7.3444-3451.1999
|View full text |Cite
|
Sign up to set email alerts
|

Development of Antibody Isotype Responses toSchistosoma mansoniin an Immunologically Naive Immigrant Population: Influence of Infection Duration, Infection Intensity, and Host Age

Abstract: We have identified the influence of host and parasite factors that give rise to characteristic antibody isotype profiles with age seen in human populations living in different areas of schistosomiasis endemicity. This is important in the immunobiology of this disease. It is also of interest in the context of human responses to chronic antigen stimulation, vaccines, allergens, and other pathogens. In populations exposed to endemic schistosomiasis, factors such as intensity and duration of infection are age depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
24
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 46 publications
(75 reference statements)
12
24
1
Order By: Relevance
“…This study confirms the results of previous studies on specific antibody responses in recently exposed communities by demonstrating that age, and/or intensity of infection and/or experience of infection influence specific antibody isotype responses against schistosome antigens, depending on the isotype Naus et al 1999). In addition, we demonstrated that treatment and subsequent re-exposure and reinfection affect anti-schistosome antibody responses and that the effect of treatment on the humoral immune response is influenced by age, intensity of infection and duration of exposure.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This study confirms the results of previous studies on specific antibody responses in recently exposed communities by demonstrating that age, and/or intensity of infection and/or experience of infection influence specific antibody isotype responses against schistosome antigens, depending on the isotype Naus et al 1999). In addition, we demonstrated that treatment and subsequent re-exposure and reinfection affect anti-schistosome antibody responses and that the effect of treatment on the humoral immune response is influenced by age, intensity of infection and duration of exposure.…”
Section: Discussionsupporting
confidence: 90%
“…As observed previously, IgG1 and IgG4 responses to SWA as well as IgG4-SEA showed a similar age profile as levels of intensity of infection, while IgE and IgA responses to SWA and SEA increased with age and SWA-and SEA-specific IgM responses were more or less similar in adults and children Ndhlovu et al 1996;Webster et al 1997;Naus et al 1999Naus et al , 2003). In contrast to previous studies on populations that were recently and chronically exposed to S. mansoni, IgG2 and IgG3 responses against SWA and SEA tended to increased with age (Webster et al 1997;Naus et al 1999Naus et al , 2003. On the other hand, our results were in concordance with those of van in a recent focus in Senegal.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…A recent example of where both age and sex were important factors in affecting the relationship between immune responses and disease was observed in a study of Schistosoma mansoni infection in a fishing community in Uganda (11). Duration of residency in an area where infections are endemic has been implicated not only in the development of antibody response profiles (12), but also in the risk of presenting with periportal fibrosis by a given age (13).…”
Section: Demographic and Genetic Influencesmentioning
confidence: 99%